Modeling and Analyzing the Variance of Wind Erosion Potential in the Badra District Center - Marwa Razzaq Khalil Thamer, Asst. Lecturer (lark, 2026)
This research aims to model and analyze the temporal variance of wind erosion potential in the Badra District Center, based on wind speed and pressure data for the period (1995–2024). The Soil Erosion Indices (BSI) and Soil Degradation Index (LDI) were also employed to monitor spatial and seasonal variations. The results showed that the dry months represent the peak of wind activity, with an average wind speed of (3.26 m/s) and an average pressure of (0.83), compared to the wet months, which recorded an average speed of (2.91 m/s) and a pressure of (0.66). This highlights the wind's ability to transport dust and sand and intensify wind erosion, especially in open areas. The year 2017 recorded the highest annual values ​​for wind speed and pressure, indicating the peak of erosion impact. The results of the BSI index showed the dominance of moderate erosion during the summer season, while low erosion expanded during the winter due to improved climatic conditions. Meanwhile, the LDI index showed a significant increase in high degradation during the winter season, reflecting the impact of water activity and surface runoff. The study concludes that seasonal and annual wind variability is a crucial factor in the dynamics of erosion and land degradation in the study area.
Keywords: Wind erosion, wind speed, wind pressure, BSI, LDI